Penanaman Mangrove di Kawasan Ekoeduwisata Bandar Bakau Dumai Sebagai Upaya Pencegahan Masalah Kesehatan - Febrian Syahputra; Timotius Agung Soripada; Tubagus Odih Rhomdani Wahid; Muhammad Faiz Adli; Annisa Salsabila Ramadhanti; Irviana Tri Adinda; Rabiatul Adawiyah; Reta Amelia Putri; Nabila Nabila; Citra Lestari Indarwati; Melinda Desvira; Zellina Shaqueela Aleem; Noor Zakiyah Khaifah; Darrel Vania Putri Vidi (Unri Conference Series: Community Engagement, 2025)
Dumai City is located on the east coast of Sumatra, facing the Strait of Malacca. Dumai's coastal location puts it at risk of disasters such as tidal flooding. Tidal flooding is a phenomenon caused by sea tides exceeding normal levels, resulting in flooding. This disaster can be very detrimental because it causes infrastructure damage and can even lead to loss of life. Furthermore, this disaster can also significantly impact the health of coastal communities. One cause is dirty floodwater mixed with waste, which can have negative health effects, especially on skin health due to direct contact with polluted water. Some examples of problems that arise include itching, irritation, bacterial or fungal infections, and other skin diseases. Various efforts can be made to prevent this incident. One effort that can be done is to prevent tidal flooding by planting mangroves and educating coastal communities about various skin problems that arise from tidal flooding. Planting mangroves is one form of prevention against seawater overflowing onto land. Mangrove ecosystems are forests that grow in coastal areas with brackish or salty water. Mangroves have strong roots that extend into the mud, providing a remarkable natural defense against tidal flooding and coastal erosion. Therefore, actions such as planting mangrove seedlings in areas adjacent to the sea can be taken as a form of environmental awareness and to anticipate tidal flooding. Based on these issues, a community service activity was carried out, namely planting 12 mangrove seedlings as a form of effort to prevent skin diseases and tidal flooding.